Key Vectors of Turkish Soft Power Policy in Georgia: Regional Dimension - Sargsyan, Hayk (Bulletin of Yerevan University D: International Relations and Political Sciences, 2019)
The region of South Caucasus has historically been an arena of competing interests for global and regional actors. Turkey, which has always been one of them, actively reen-gaged into the region after the collapse of the Soviet Union. Not only did Turkey realize Georgia's crucial importance as a transit country of the Caspian energy resources, but it also viewed Georgia as a link with Azerbaijan and Central Asian republics. Therefore, immediately after the collapse of the Soviet Union Turkey set up intensive cooperation with Georgia also making use of soft power tools. The aim of this article is to explore the peculiarities of Turkish soft power in Georgia, to examine its main components and to outline the importance of soft power for bilateral relations.